Reversible chirality inversion of circularly polarized luminescence in a photo-invertible helical cholesteric superstructure. Issue 97 (19th November 2019) - Qiao, Jinghui; Lin, Siyang; Li, Juntao; Tian, Jiajun; Guo, Jinbao
Abstract : The first example of photo-driven reversible chirality inversion of circularly polarized luminescence in a helical cholesteric superstructure is reported. Abstract : A photo-invertible helical cholesteric superstructure was constructed by doping a novel chiral fluorescence photoswitch and a static dopant with opposite handedness into a nematic host. The handedness of circularly polarized luminescence can be reversibly inverted accompanied by a positive–negative change of luminescence dissymmetry factor values upon alternate light irradiations.